Two new species and one new record of Willowsia Shoebotham, 1917 (Collembola: Entomobryidae) from the Eastern Himalayan region of India - Mandal, Pritha; Mandal, Guru Pada; Suman, Kusumendra Kumar; Bhattacharya, Kaushik Kumar (European Journal of Taxonomy, 2024)
Two species new to science Willowsia sikkimensis sp. nov. and W. arunachalensis sp. nov., and one new record of the genus Willowsia Shoebotham, 1917 are described and illustrated here. The new species are mainly distinguished from the others on the basis of pigment pattern, scale type and chaetotaxy. The species were collected from the states of Arunachal Pradesh and Sikkim (India). Willowsia shiae Pan, Zhang & Chen, 2006 is recorded for the first time from India (Arunachal Pradesh) and redescribed with detailed chaetotaxic nomenclature. A key to the Indian species of Willowsia and a comparison table of related species are also provided.